THE NORTHERN LIMIT LINE (NLL) AGREEMENT BETWEEN SOUTH AND NORTH KOREA ON THE MARITIME BORDER IN THE YELLOW SEA - Widiyatmoko Baruno Aji; Chomariyah Chomariyah; Wisnu Aryo Dewanto (JOURNAL ASRO, 2021)
The division of Korea into North and South Korea began with the victory of the Allied Powers in World War II, which ended 35 years of Japanese occupation of Korea. The maritime boundaries of the West Sea and East Sea of Korea are not clearly regulated in the Armistice Agreement of 1953. In particular, maritime restrictions on the Yellow Sea are seen as important in relation to the management of the region's large fishery resources. In 1953 the UN Command unilaterally declared the NLL (Northern Limit Line) along the five western islands, as the de facto maritime border in the Yellow Sea. North Korea, which is an NLL farmer, threatens a conflict of legality so that there is a continuous conflict so that efforts are needed to help the conflict between the two countries. Keywords: Korea, Northern Limit Line, United Nation Security Council